PERANCANGAN ALAT SISTEM KONTROL KETINGGIAN AIR DENGAN MENGGUNAKAN METODE PROTOTYPE BERBASIS ARDUINO - Malau, Yohanes Gervasius Vandher Yovi; Nopriadi, Nopriadi (Computer Science and Industrial Engineering, 2023)
Making a water level control system using the Arduino-based prototyping method means making a tool to regulate the water level of the pool automatically. The Arduino platform is used to develop the system, which serves as the main regulator that can control various related components and sensors. The prototype design process enables rapid development of iterative control systems. The system was developed and upgraded to meet the desired performance requirements by using Arduino modules, water pump actuators, water level sensors, and additional components such as LCDs, ultrasonic sensors, buzzers, and relays. At first, the water level sensor is used to measure the water level in the tank. The data from the sensor is processed by the Arduino, and a corresponding control signal is generated. This control signal regulates the water pump to discharge water from the tank according to the set point. When developing this prototype, an important factor to consider is the accuracy and reliability of the control system. When designing this tool, scalability and ease of use were also considered. It is expected that this water level control system tool can provide efficient water level regulation solutions for various applications, such as agricultural irrigation, automatic irrigation systems, water level control storage tanks, and others, using an Arduino-based tool approach.